Perbedaan Pemberian Jus Apel Hijau dan Air Rebusan Daun Seledri terhadap Tekanan Darah Wanita Menopause Hipertensi di Kabupaten Bojonegoro - Lia Rohmatin; Tri Yunita Fitria Damayanti; Idcha Kusma Ristanti (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Hypertension or high blood pressure is a chronic condition characterized by increased blood pressure on the walls of the arteries. Hypertension is caused by high sodium intake while vegetable and fruit intake is low. This study aims to determine the difference in blood pressure reduction in groups given green apple juice and boiled water from celery leaves in menopausal women who experience hypertension in Bojonegoro Regency. This type of research is quantitative research with a "True experimental" design, with a "Two Group Pre-test and Post-test Design". This sample consisted of 36 respondents who were divided into 18 respondents of green apple juice and 18 respondents of boiled celery leaf water using a purposive sampling technique. Data collection using a Stethoscope Tensimeter measuring instrument and observation sheets will be analyzed using the Paired T-Test and Independent Sample T-Test. The research results were analyzed using the Paired T-Test, it was found that there was a significant difference in systolic blood pressure (p-value = 0.003) and diastolic blood pressure (p-value 0.032) before and after administration of green apple juice. In the celery leaf boiled water group, significant results were also found to reduce systolic blood pressure (p-value = 0.000) and diastolic blood pressure (p-value = 0.017) before and after administering celery leaf boiled water. From the description above, it can be concluded that giving green apple juice and boiled water from celery leaves can significantly reduce systole and diastole. Keywords: green apple, celery, hypertension, menopausal women